Extrudability of geopolymers and control of the formed networks by zeta potential and NMR spectroscopy - Wilfried Cyrille N'Cho; Ameni Gharzouni; Isabel Sobrados; Jenny Jouin; Anne Aimable; Sylvie Rossignol (International Journal of Ceramic Engineering & Science)
Abstract In this study, the local‐scale structure of geopolymers shaped by extrusion or 3D printing was investigated and correlated to the reactivity of the raw materials. The reactivity of the different metakaolin mixtures was evaluated using zeta potential measurements with different alkali silicate solutions, followed by shaping via 3D printing; additionally, the different networks formed were identified via NMR spectroscopy. The results showed that in the presence of weakly reactive basic solutions, the Al(OH)4− species were released in low amounts due to an increase in the polymerized silicate species in the solution, resulting in a low zeta potential in absolute value. Conversely, for more reactive solutions, the silicate species were more depolymerized, and the siliceous and aluminous metakaolin species were more easily released in solution, resulting in increasingly low zeta potential values. Some samples were 3D printed with metakaolin mixtures using different printers and silicate solutions (K, KNa) with alkaline cation concentrations of [M] > 2.8 M in the mixtures; here, the metakaolin zeta potential values were greater than −50 mV, and the local‐scale structure consisted of more than 50% geopolymer networks (Q4(3Al) + Q4(2Al)).